Polyphony in action: interdisciplinary approaches and sustainable strategies for musical cultural heritage preservation - Zhe Tang; Ennan Wu (Humanities & Social Sciences Communications)
Abstract Musical Cultural Heritage Preservation (MCHP) is a complex, multidimensional global challenge that intertwines historical memory, cultural identity, and social transformation. Employing Bakhtin’s theory of ‘polyphony’ as a metaphorical framework and utilizing CiteSpace for bibliometric analysis, this study systematically examines research trends in MCHP from 2000 to 2024. Key findings include: (1) Current research is predominantly concentrated in developed countries, while the culturally rich Global South remains underexplored; (2) Four major research themes are identified: economic and industrial development of heritage, cultural identity and critical heritage studies, technological applications (e.g., digitization and AI), and ecological linkages; (3) Traditional and popular music persist as focal topics, with emerging trends such as the ‘second life’ of folk culture and digital innovation gaining momentum; (4) Future efforts should prioritize interdisciplinary collaboration, embrace polyphonic diversity through listening practices and dynamic revitalization, and integrate ecological perspectives to transition heritage from ‘static preservation’ to ‘living symbiosis.’ The study advocates decentralizing authoritative narratives, amplifying marginalized voices, and fostering community-driven strategies to ensure the sustainability of musical heritage in a globalized world.